Sexism and Homophobia in Adolescents of a Public Educational Institution - Bernuy Castromonte, Breiding Junior (2017)
The research explores the relationship between sexism and homophobia in adolescents of a public educational institution in Chimbote. The research design was descriptive - correlational and a sample of 406 students between males and females from 1st to 5th level of secondary education. As a measure they were evaluated with the Scale of Detection of Sexism of Ramos, Cuadrado and Recio (2007) adaptation of Acosta (2010) and the scale of modern homophobia of Raja and Stokes (2005) adaptation of Paredes (2013). The results of the research reflect a very significant, direct and strong relationship that indicates that the more sexism in adolescents, the more homophobic attitudes they can show. For hostile sexism and homophobia towards gay, a correlation of (r =.641 ** p <.01) and for lesbians (r =. 658 ** p <.01) was obtained; between gay sexism and homophobia towards gay (r =.574 ** p <.01) and towards lesbians (r =.646 ** p <.01). Levels of sexism by gender are identified as a high level of hostile and benevolent sexism for the male population with 14.1% and 15.7% respectively. There are also levels of homophobia according to gender in adolescents to gay and lesbian people with 35.3% and 25.3%